Role of prophylactic central compartment lymph node dissection in clinically N0 differentiated thyroid cancer patients: analysis of risk factors and review of modern trends. Issue 1 (December 2016) - Conzo, Giovanni; Tartaglia, Ernesto; Avenia, Nicola; Calò, Pier; de Bellis, Annamaria; Esposito, Katherine; Gambardella, Claudio; Iorio, Sergio; Pasquali, Daniela; Santini, Luigi; Sinisi, Maria; Sinisi, Antonio; et al.
Abstract In the last years, especially thanks to a large diffusion of ultrasound-guided FNBs, a surprising increased incidence of differentiated thyroid cancer (DTC), "small" tumors and microcarcinomas have been reported in the international series. This led endocrinologists and surgeons to search for "tailored" and "less aggressive" therapeutic protocols avoiding risky morbidity and useless "overtreatment". Considering the most recent guidelines of referral endocrine societies, we analyzed the role of routine or so-called prophylactic central compartment lymph node dissection (RCLD), also considering its benefits and risks. Literature data showed that the debate is still open and the surgeons are divided between proponents and opponents of its use. Even if lymph node metastases are commonly observed, and in up to 90 % of DTC cases micrometastases are reported, the impact of lymphatic involvement on long-term survival is subject to intensive research and the best indications of lymph node dissection are still controversial. Identification of prognostic factors for central compartment metastases could assist surgeons in determining whether to perform RLCD. Considering available evidence, a general agreement to definitely reserve RCLD to "high-risk" cases was observed. More clinical researches, in order to identify risk factors of meaningful predictive power and prospective long-term randomized trials, should be useful to validate this selective approach.